Coefficient estimates for two subclasses of analytic and bi-univalent functions - Lashin, A. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce two new subclasses of the class σ of analytic and bi-univalent functions in the open unit disk U. Furthermore, we obtain the estimates for the first two Taylor – Maclaurin coefficients |a_2| and |a_3| for the functions from these new subclasses.